177k views
5 votes
911!!! please answer this!!!

911!!! please answer this!!!-example-1

2 Answers

5 votes

Answer:

Explanation:

Fourth option

User Davidhigh
by
4.6k points
1 vote


\left((3a^(-3)b^2)/(2a^(-1)b^0)\right)^2

First some simplifying:


\left((3a^1b^2)/(2a^3b^0)\right)^2=\left((3b^2)/(2a^2)\right)^2=(9b^4)/(4a^4)

Then with
a=-2 and
b=-3, we have
a^4=(-2)^4=16=4^2 and
b^4=(-3)^4=81=9^2, so


(9b^4)/(4a^4)=(9\cdot9^2)/(4\cdot4^2)=(9^3)/(4^3)=(729)/(64)

User Bracken
by
5.0k points